Analysis of Algebra Questions in Curriculum 2013 and Merdeka Curriculum Mathematics Textbooks - Wahyuni, Hesti; Iskandar, Ratu Sarah Fauziah; Raditya , Aji; Talde, Danna Karyl Jane C. (EDUPEDIA Publisher, 2023)
The purpose of this study is to analyze problems in the mathematics textbook of the 2013 curriculum and the independent curriculum in algebra material. This is used to find out what students should do to answer questions on problems in math textbooks. The method used in this study is a five-dimensional analysis method, consisting of: mathematical activity, problem complexity, contextual situation, process and type of answer. Data collection techniques are carried out by analyzing and describing the types of algebra problems in the mathematics textbooks of the 2013 curriculum and the independent curriculum. The results of this study show that algebra problems in the 2013 curriculum textbooks and the independent curriculum emphasize calculating/using various calculation operations by 63.78% in the 2013 curriculum and 40.23% in the independent curriculum, direct application of basic knowledge/skills by 68.65% in the 2013 curriculum and building/making connections by 59.77% in the independent curriculum, questions without context amounted to 62.16% in the 2013 curriculum and questions with real-world context amounted to 46.55% in the independent curriculum, using mathematical concepts, facts, procedures and reasoning amounted to 76.76% in the 2013 curriculum and 58.62% in the independent curriculum, closed answers amounted to 63.78% in the 2013 curriculum and 74.14% in the independent curriculum.